2018
DOI: 10.1039/c8nr02793e
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-based plastic absorber for total sub-terahertz radiation shielding

Abstract: Increasing the requirements on telecommunications systems such as the need for higher data rates and connectivity via the Internet of things results in continuously increasing amounts of electromagnetic radiation in ever-higher telecommunications bands (up to terahertz). This can generate unwanted electromagnetic radiation that can affect the operation of electronic devices and human health. Here, we demonstrate that nonconductive and lightweight, graphene-based composites can shield more than 99.99% of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…In the broad terahertz range 0.3-2.1 THz, a linear relation between SWNT loading and SE has been found. In the low frequency range 0.3-0.6 THz, the SE exhibits low F I G U R E 6 Shielding effectiveness of carbon-based composites at 0.5-0.6 THz; a -Macutkevic et al (2012), [30] b -Macutkevic et al (2012), [29] c -Macutkevic et al (2008), [31] d -Zdrojek et al (2018), [38] e -Das et al (2011), [28] f -Seo et al (2008), [27] g -Huang et al(2018), [39] h -Das et al (2012), [33] i -Venkatachalam et al, [40] j -Polley et al [41] values (10 dB) and the transmittance reaches 60%. However, the transmittance dropped almost to zero for frequencies above 2 THz.…”
Section: Carbon-based Polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the broad terahertz range 0.3-2.1 THz, a linear relation between SWNT loading and SE has been found. In the low frequency range 0.3-0.6 THz, the SE exhibits low F I G U R E 6 Shielding effectiveness of carbon-based composites at 0.5-0.6 THz; a -Macutkevic et al (2012), [30] b -Macutkevic et al (2012), [29] c -Macutkevic et al (2008), [31] d -Zdrojek et al (2018), [38] e -Das et al (2011), [28] f -Seo et al (2008), [27] g -Huang et al(2018), [39] h -Das et al (2012), [33] i -Venkatachalam et al, [40] j -Polley et al [41] values (10 dB) and the transmittance reaches 60%. However, the transmittance dropped almost to zero for frequencies above 2 THz.…”
Section: Carbon-based Polymer Compositesmentioning
confidence: 99%
“…Recently Zdrojek et al. [ 38 ] presented a series of nonconductive PDMS composites containing three different contents of graphene flakes inclusions (0.1, 0.2, and 10 wt.%), fabricated via a simple blend‐mixing method. The samples in form of flat disks, approximately 0.8 mm thick were tested within 0.1–0.8 THz using a custom made THz‐TDS setup.…”
Section: Carbon‐based Materialsmentioning
confidence: 99%
“…The specific nanofiller loading was chosen based on our previous works on PDMS composites containing graphene inclusions, where we showed the influence of graphene loading on optical properties of fabricated composites. 10,20 For reference, a sample containing no additives was also fabricated. All composites were fabricated in the form of a flat flexible slab 700 μm ± 20% thick (see Figure 1(b)).…”
Section: Sample Fabricationmentioning
confidence: 99%
“…Compared with shielding materials based on the reflective mechanism, THz absorption materials demand both a very low reflection and transmission, which can eliminate THz radiations in the environment. For example, Zdrojek et al demonstrated a graphene‐based plastic absorber, and more than 99.99% of the electromagnetic energy is shielded via absorption in the sub‐THz range. The porous materials have a better shielding performance for their larger porosity .…”
Section: Introductionmentioning
confidence: 99%